Nutrient Indexing in "'Kinnow" Mandarin (Citrus deliciosia Lour.× Citrus nobilis Tanaka) Grown in Indogangetic Plains. Issue 18 (10th October 2016) - Srivastava, A. K.; Patil, Prakash
ABSTRACT: Diagnosis and remediation of nutrient constraints in perennial fruit crop like citrus are the two important pillars of an effective nutrient management program. Efforts were made to develop nutrient indexing (NI) criteria based on generated leaf and soil analysis dataset for "Kinnow" mandarin ( Citrus deliciosia Lour. × Citrus nobilis Tanaka) grown on illitic soils of Indogangetic plains (Entisol, Inceptisol, and Aridisol). NI through diagnosis and recommendation integrated system (DRIS) using leaf analysis data showed optimum value of leaf nutrient concentration as 2.22–2.32% nitrogen (N), 0.11–0.15% phosphorus (P), 1.10–1.41% potassium (K), 2.32–2.79% calcium (Ca), 0.38–0.61% magnesium (Mg), 22.4–58.3 ppm iron (Fe), 26.3–56.2 ppm manganese (Mn), 4.2–7.2 ppm copper (Cu), and 21.3–26.9 ppm zinc (Zn) vis-à-vis a fruit yield of 32.4–56.1 kg tree −1 . Using these NI criteria, Zn was observed as most deficient (64.7%) followed by Fe (61.5%), Mn (57.6%), N (96.1%), and P (38.5%) using percentage of orchards as basis. While, optimum NI (mg kg −1 ) using soil analysis data was determined as 114.3–121.2 potassium permanganate (KMnO4 -N), 7.8–12.3 Olsen-P, 96.4–131.3 ammonium acetate (NH4 OAc)-K, 189.4–248.6 NH4 OAc-Ca, 72.3–89.9 NH4 OAc-Mg, 5.8–11.1, DTPA-Fe, 4.3–6.9 diethylenetriaminepentaacetic acid (DTPA)-Mn, 0.45–0.69 DTPA-Cu, and 21.3–26.9 DTPA-Zn for the optimum yield of 32.4–56.1 kg tree −1 . Soil analysis-based NIs displayed a good complementary with leaf analysis-based NIs evident from the diagnoses indicating Mn (52.2%) as most dominant constraint Zn (61.2%) followed by Mn (48.3%), N (41.2%), and P (35.6%). The recommended DRIS-based NIs would lay a scientific basis in formulating citrus fertilization program.